2019
DOI: 10.1017/s0140525x18002571
|View full text |Cite
|
Sign up to set email alerts
|

Emotions in the development of moral norms within cooperative relationships

Abstract: We support May's criticism of attempts to reduce morality to being primarily based on evolved emotional reactions. However, we question the clarity and consistence of his own position and suggest taking a developmental approach. We focus on providing a developmental approach to the role of emotions in the social origin of moral norms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0
3

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 14 publications
0
3
0
3
Order By: Relevance
“…Considering one aspect of the psychological patterns of personal growth -cognitive and emotional unity in process, we highlight such a significant component of the values formation as emotions/experiences (Blackman, 2019;Carpendale & Wallbridge, 2019;Haidt, 2006). Jonathan Haidt's research presents the essence of the emotional content of moral values, revealed through the observance of social and moral norms, thus creating a "feeling of happiness" (Haidt, 2006).…”
Section: Theoretical Substantiation Of the Essence Of The Moral Value...mentioning
confidence: 99%
See 2 more Smart Citations
“…Considering one aspect of the psychological patterns of personal growth -cognitive and emotional unity in process, we highlight such a significant component of the values formation as emotions/experiences (Blackman, 2019;Carpendale & Wallbridge, 2019;Haidt, 2006). Jonathan Haidt's research presents the essence of the emotional content of moral values, revealed through the observance of social and moral norms, thus creating a "feeling of happiness" (Haidt, 2006).…”
Section: Theoretical Substantiation Of the Essence Of The Moral Value...mentioning
confidence: 99%
“…Reid Blackman argues this statement by explaining the nature of moral motivation through the influence of emotions and the reasons for them to arise (Blackman, 2019). Their formation successfully ensures the implementation of a "developmental approach to the role of emotions in the social origin of moral norms," the application of which allows taking into account the specifics of the emotional sphere of each individual (Carpendale & Wallbridge, 2019). It confirms the position that the level of moral maturity of the individual is determined by the formation of all moral values components and is based on awareness and adherence to the system of social values.…”
Section: Theoretical Substantiation Of the Essence Of The Moral Value...mentioning
confidence: 99%
See 1 more Smart Citation
“…A distribuição de vagas educacionais, como recursos escassos e atrelados às oportunidades de ascensão social demandam julgamentos pautados não na competição e concorrência. A demanda educacional deveria ser pautada na cooperação, promovendo objetivos coletivos, treinando a colaboração, não a concorrência (Carpendale & Wallbridge, 2019;Kesselring, 2011). Para que esse ideal seja alcançado, o respeito ou reconhecimento das diversas situações educacionais e desigualdades raciais e sociais é fundamental.…”
Section: Discussionunclassified
“…Para além da imposição legal, a percepção individual a respeito da justiça da utilização de cotas nas universidades, se torna essencial para o estabelecimento de relações de cooperação no ambiente acadêmico (Carpendale & Wallbridge, 2019). A solidariedade e o respeito mútuo são fruto de relações cooperativas e são fundamentadas nos princípios de justiça (Carpendale & Lewis, 2006;Piaget, 1932Piaget, /1994.…”
Section: Estudo -Protocolounclassified